Gait mechanics after ACL reconstruction: implications for the early onset of knee osteoarthritis. Issue 5 (28th November 2008) - Butler, R J; Minick, K I; Ferber, R; Underwood, F
Abstract : Background: Individuals who sustain a rupture of the anterior cruciate ligament (ACL) are at an increased risk for developing early-onset knee osteoarthritis (OA). The mechanism behind the early onset of the disease is still unknown. Knee OA progression has been previously examined by calculating the internal knee-abduction moment during gait. However, knee-joint moments have not been examined in individuals after ACL reconstruction as a potential mechanism for disease progression in early knee OA. Objective: To determine if individuals who have undergone ACL reconstruction exhibit altered gait mechanics that may be associated with knee OA progression. Methods: In total, 17 people who had previously undergone ACL reconstruction were enrolled in the study. A matched control group was recruited for comparison. All participants underwent gait analysis at an intentional walking speed to examine variables previously associated with knee OA progression, primarily the internal peak knee-abduction moment, during gait. One way ANOVAs were performed to examine differences in gait mechanics between the two groups. All joint moments were calculated as internal moments. Results: The peak knee-abduction moment was increased by 21% in the ACL compared with the control group (p = 0.04). No other differences were seen in frontal plane knee or hip mechanics. Conclusion: It seems that individuals who have undergone ACL reconstruction exhibit an increased peak knee-abduction moment that may establish a potential mechanism of the earlier onset of knee OA in this population.